The Legacy of Girls and Sisters Between Islamic Fiqh and The Law Into a Legal Comparative Study to Islamic Fiqh (Raparin Journal of Humanities (RJH), 2020)
This research summarizes the study of a vital issue of women’s controversial issues, which is the issue of women's inheritance, and the controversy surrounding them had a clear impact on the attitudes of legislators and judicial decisions in Islamic countries in general.The efforts of civil society organizations and women's rights calling for equal inheritance between men and women have affected the orientations of the Iraqi legislator in various periods and have led to changes in the inheritance materials, especially those related to the inheritance of girls and sisters, and the legacy of grandchildren and children of brothers and sisters, the most recent of which is the numbered amendment law ( 15) Issued by the Kurdistan Region Parliament in the year 2008 called the Law Amending the Application of the Personal Status Law No. (188) for the year 1959 amended in the Kurdistan Region - Iraq.This research aims to study the inheritance of girls and sisters between Islamic jurisprudence and the law in accordance with the Iraqi Personal Status Law No. (88) for the year 1959 AD and its amendments related to their inheritance study and a comparative study and its effects in terms of inheritance by imposition, intolerance, restitution, and blocking. Through a descriptive, investigative, analytical approach, he sheds light on the explanation's varying interpretations of the legal materials related to inheritance, especially the inheritance of girls and sisters.The research plan included two studies, the first topic was devoted to studying cases of the inheritance of girls and the inheritance of the daughters of the son, jurisprudence and law, and the differences between them, and the second topic was devoted to studying cases of inheritance of sisters with their three types, jurisprudence and law, and the differences between them. The research concluded with the most important results and a number of recommendations.